syn Additions to 4α-Epoxypyranosides: Synthesis of L-Idopyranosides - Cheng, Gang (2007)
[Image: see text] The syn-selective addition of organozinc compounds to 4α-epoxypyranosides (4α-EPs), generated from methyl β-D-glucoside or aminoglucoside, provides an efficient route to pyranosides with α-L-ido configurations, including L-iduronic acid, neosamine B, and higher monosaccharide derivatives.